Pathloss Model of Distance Independent for Indoor Area - Rumin Yang; Qiyi Dai; Chengbo Yu (Dianxin kexue)
A pure statistical indoor path-loss model was proposed with an eye to address the problems of distance dependence and of line-of-sight（LOS）or non-LOS uncertainty，which lie in most conventional path-loss models.In the model，the path length（distance）was taken as a random variable，and the uncertainty of LOS or NLOS was represented by an alternating frequency between LOS and non-LOS channel conditions.Without knowing the priori path length，the model can estimate or predict the loss of path based on the priori knowledge of the radius of operating space，of the LOS/NLOS alternating frequency and of a confidence interval describing the path quality.In addition，three quality of services（QoS）for different quality requirements were proposed in order to conserve energy.As opposed to assuming fixed available power or covering the largest possible distance，which is typical in conventional models，the QoS-oriented model has significant advantages on resource allocation and energy conservation.Through a case study，it is indicated that this model is simple and practical.